Mr Standfast - Buchan, John 1875-1940 (The world's classics, 1993)
In Mr Standfast (1919), the third of the four novels featuring Richard Hannay, we meet again Pieter Pienaar and John S. Blenkiron, who are joined by the spirited Mary Lamington. It is 1917 and Hannay is brought out of the battlefield to perform the desperate task of tracking down and destroying a network of German spies. Hannay's opponent is Morton Ivery, the bland master of disguise, who seeks to outwit Hannay as he and his agents are pursued through England, Scotland, France, and Switzerland. For its pace and suspense, its changes of scene, and thrilling descriptions of the last great battles against the Germans, Mr Standfast offers everything that has made its author so enduringly popular.